2018
DOI: 10.2355/isijinternational.isijint-2017-642
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Elastic Anisotropy in Williamson-Hall Plots by Diffraction Young’s Modulus and Direct Fitting Method

Abstract: It is known that the micro-strain in cold worked iron can be evaluated by the classical Williamson-Hall method using the three data of diffraction peaks: {110}, {211} and {220}. It is not clarified that the obtained value gives the true micro-strain or not. In addition, the accuracy of analysis is not so high because the diffraction strength from {220} plane is generally very weak. In this paper, three methods, i.e. classical Williamson-Hall method, Diffraction Young's Modulus Correction method and Direct Fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
(46 reference statements)
3
24
0
Order By: Relevance
“…In this section, we show that the Bragg-edge broadenings of diffraction indices 110, 200, 211, 220, 310 and 321 are consistent with those of the corresponding diffraction peaks. Then, we also show that the corrected classical Williamson-Hall (ccWH) plots 25) of the Bragg-edge data are proportional to the magnitude of the scattering vector corrected by the ratio of the diffraction Young's modulus. Finally, we discuss the validity of parameters obtained from the ccWH plot, by comparing with the results of previous diffraction studies.…”
Section: Classical Williamson-hall Plot With the Crystal Elastic Anismentioning
confidence: 73%
See 4 more Smart Citations
“…In this section, we show that the Bragg-edge broadenings of diffraction indices 110, 200, 211, 220, 310 and 321 are consistent with those of the corresponding diffraction peaks. Then, we also show that the corrected classical Williamson-Hall (ccWH) plots 25) of the Bragg-edge data are proportional to the magnitude of the scattering vector corrected by the ratio of the diffraction Young's modulus. Finally, we discuss the validity of parameters obtained from the ccWH plot, by comparing with the results of previous diffraction studies.…”
Section: Classical Williamson-hall Plot With the Crystal Elastic Anismentioning
confidence: 73%
“…22) On the other hand, Takaki et al have reported that the corrected classical WH method, the ccWH method, in which the crystal elastic anisotropy is corrected by the ratio of diffraction Young's modulus, is usable for dislocation density evaluation of a low-carbon ferritic steel. [23][24][25][26] We applied the ccWH method in our feasibility study because the sample condition was similar to that of Takaki's study, although the goal in the future is to apply the mWH/mWA method. In any case, various evaluation methods for micro-strain, dislocation density/arrangement/ character and crystallite size, using the diffraction peak line-broadening/profile analysis, have been proposed and applied in materials science and engineering.…”
Section: Simultaneous Broadening Analysis Of Multiple Bragg Edges Obsmentioning
confidence: 99%
See 3 more Smart Citations